2021
DOI: 10.1126/scitranslmed.abc7804
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of mRNA-encoded cytokines promotes antitumor immunity and tumor eradication across multiple preclinical tumor models

Abstract: Local immunotherapy with an mRNA mixture encoding four cytokines mobilizes a systemic antitumor response and promotes tumor eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 46 publications
3
83
0
Order By: Relevance
“…For example, the short half-life requires frequent administration, leading to dose-limiting toxicity. Existing preclinical studies demonstrated that the toxic side effects of systemic administration can be avoided by intratumoral administration ( 96 , 97 ). In addition, the main active site of immunostimulants is in the TIME, so clinical studies have mainly adopted intratumoral injection.…”
Section: Clinical Development Of Mrna Cancer Vaccinementioning
confidence: 99%
“…For example, the short half-life requires frequent administration, leading to dose-limiting toxicity. Existing preclinical studies demonstrated that the toxic side effects of systemic administration can be avoided by intratumoral administration ( 96 , 97 ). In addition, the main active site of immunostimulants is in the TIME, so clinical studies have mainly adopted intratumoral injection.…”
Section: Clinical Development Of Mrna Cancer Vaccinementioning
confidence: 99%
“…Saline-formulated mRNA for four cytokines gene (IL-2, IL-15, IFN-α, and GM-CSF) when administered at the tumor site led to systemic antigen-specific T cell expansion, granzyme B + T cell infiltration, and immunological memory development. Moreover, profound tumor regression was identified when this mRNA-based cytokine therapy was combined with immunomodulatory agents [ 56 ].…”
Section: Targeting Time Using Rna-based Platformsmentioning
confidence: 99%
“…For example, co-delivery of stimulatory cytokines, such as GM-CSF, IL-12, and IL-15, with mRNA encoding tumor antigen in dendritic cell vaccines promotes remodeling of the TME, enhances cytotoxic T cell responses, and controls tumor growth in preclinical models (128)(129)(130)(131). Further, in situ vaccination with a cocktail of naked mRNAs encoding IL-12, GM-CSF, IL-15, and IFN-α4 promotes tumor infiltration of polyfunctional Th1-like CD4 + cells, cytotoxic CD8 + T cells, and pro-immune monocytic cell types while decreasing Tregs, leading to survival benefits in murine models of cancer including metastatic melanoma (132). Similarly, in melanoma patients, coexpression of immunostimulatory molecules, such as CD40L, CD70, and constitutively active TLR4 (TriMix, eTheRNA Immunotherapies), along with the tumor antigen mRNA potentiates APC maturation and cognate T cell activation (133,134).…”
Section: Biologic and Immunologic Qualities Underpinning Mrna Vaccine...mentioning
confidence: 99%